The call of the wild - LONDON, JACK; JACK LONDON (New York Aladin Paperbacks, 1994)
Buck, a pampered dog kidnapped from California and sold as a sled dog during the Klondike Gold Rush.
Keywords: stolen from his comfortable California home and sold as a sled dog in the Yukon during the 1890s Klondike Gold Rush; survival requires adapting to harsh realities by embracing one's inner instincts, tenacity, and strength